STUDI SIFAT FISIK, KIMIA DAN FUNGSIONAL TEPUNG KACANG MERAH DAN TEPUNG TEMPE KACANG MERAH (Phaseolus vulgaris L.) - Ruben, Elisabet; Wisaniyasa, Ni Wayan; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2016)
This research aims to know differences in the physical, chemical, and functional properties of red kidney beans and red kidney beans tempeh flour. Data were analyzed by paired t-test at the 95% confidence interval using SPSS (Statistical Program for Social Science). The results showed that there are differences in the physical properties is bulk density, the chemical properties are water content, ash content, fat content, carbohydrate content, and the functional properties are water absorption capacity, oil absorption capacity, swelling power, solubility, while there are no differences in color test, and protein content. The results of research showed that red kidney bean flour for bulk density (0.58g/ml), color test (L value (44.08), a value (-4.65), b value (13.63)), water content (6.79%bb), ash content (3.33%bb), fat content (12.56%bb), protein content (9.04%bb), carbohydrates content (68.28%bb), water absorption capacity (246.04%), oil absorption capacity (91.14%), swelling power (4.27g/g), and solubility (12.12%), while the red kidney beans tempeh flour for bulk density (0.54g/ml), color test (L value (41.08), a value (-6.45), b value (15.83)), water content (8.26%bb), ash content (2.14%bb), fat content (7.11%bb), protein content (9.87%bb), carbohydrates content (72.62%bb), water absorption capacity (277.81%), oil absorption capacity (99.00%), swelling power (4.75g/g), and solubility (21.67%).
Keywords: red kidney bean, tempeh, flour